2008
DOI: 10.1073/pnas.0808719105
|View full text |Cite
|
Sign up to set email alerts
|

Temporal control of the dephosphorylation of Cdk substrates by mitotic exit pathways in budding yeast

Abstract: The temporal phosphorylation of cell cycle-related proteins by cyclin-dependent kinases (Cdks) is critical for the correct order of cell cycle events. In budding yeast, CDC28 encodes the only Cdk and its association with various cyclins governs the temporal phosphorylation of Cdk substrates. S-phase Cdk substrates are phosphorylated earlier than mitotic Cdk substrates, which ensures the sequential order of DNA synthesis and mitosis. However, it remains unclear whether Cdk substrates are dephosphorylated in tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 28 publications
2
53
0
Order By: Relevance
“…Unexpectedly, the Cdc14-dependent dephosphorylation of Dsn1 occurs prior to anaphase when Cdc14 is sequestered in nucleolus and the bulk of known Cdc14 targets are not dephosphorylated, including the Fin1 kinetochore protein that is readily dephosphorylated by Cdc14 at the onset of anaphase (e.g., Shou et al 1999;Visintin et al 1999;Jaspersen and Morgan 2000;Pereira and Schiebel 2003;Jin et al 2008;Akiyoshi et al 2009;Konig et al 2010). To our knowledge, this is the first observation of a nonnucleolar protein that is dephosphorylated in a Cdc14-dependent manner prior to anaphase onset, suggesting that there is a pool of active Cdc14 outside of nucleolus.…”
mentioning
confidence: 99%
“…Unexpectedly, the Cdc14-dependent dephosphorylation of Dsn1 occurs prior to anaphase when Cdc14 is sequestered in nucleolus and the bulk of known Cdc14 targets are not dephosphorylated, including the Fin1 kinetochore protein that is readily dephosphorylated by Cdc14 at the onset of anaphase (e.g., Shou et al 1999;Visintin et al 1999;Jaspersen and Morgan 2000;Pereira and Schiebel 2003;Jin et al 2008;Akiyoshi et al 2009;Konig et al 2010). To our knowledge, this is the first observation of a nonnucleolar protein that is dephosphorylated in a Cdc14-dependent manner prior to anaphase onset, suggesting that there is a pool of active Cdc14 outside of nucleolus.…”
mentioning
confidence: 99%
“…In support of the negative role of Clb5 in anaphase, we have shown that overexpression of CLB5 results in the accumulation of large budded cells with an undivided nucleus. 16 In summary, Clb5-Cdk1 promotes the initiation of DNA synthesis by phosphorylating DNA synthesisrelated proteins. However, on the other hand, Clb5-Cdk1 plays a negative role in anaphase by phosphorylating microtubule-associated proteins before anaphase onset.…”
Section: The Positive and Negative Roles Of Clb5 In Cell Cycle Progrementioning
confidence: 99%
“…The loss of function of the phosphatase Cdc14 abolishes the dephosphorylation of both Sld2 and Pol12, suggesting that either FEAR or MEN-dependent Cdc14 release is required for the dephosphorylation of both Clb5 and Clb2 substrates. 4,16 The FEAR-induced Cdc14 release during early anaphase raises the possibility that the FEAR pathway contributes to the dephosphorylation of Clb5 substrates immediately after anaphase onset. We found that the inactivation of the MEN pathway prevents the dephosphorylation of Clb2 substrate, but the Clb5 substrate is still able to be dephosphorylated.…”
Section: The Relationship Between the Two Mitotic Pathways And The Dementioning
confidence: 99%
See 2 more Smart Citations